Sintesis, Karakterisasi dan Sifat Optik Graphene Oxide (GO) berbasis Bahan Alam Tempurung Kelapa - Nikmah, Ainun; Kurniawan, Robi (Jurnal Penelitian Sains, 2024)
In this study, graphene oxide (GO) was successfully synthesized using the modified Hummer method. GO was synthesized using natural raw materials from coconut shell waste. The synthesis sample was characterized using XRD, FTIR, and SEM EDX. The XRD results showed that there were 2 main peaks corresponding to the hkl 002 and 100 planes. The XRD results showed that the synthesis sample tended to form reduced graphene oxide compounds (rGO). The functional group of the FTIR results showed that the GO formed was not completely reduced to rGO which was indicated by the presence of C-H stretching at a wave number of 3065 cm-1. In addition, there were also two C=O peaks in the alkoxy and epoxy groups which were characteristic of GO. The sample's morphology from the SEM results showed a typical structure of GO, namely forming a thin layered sheet with a thickness of around 14.57 to 14.86 nm. The optical properties of GO were also investigated using UV Vis and the energy band gap value was obtained around 2.97 eV.